A neglected complication of COVID-19: liver injury - Tian LAN; Xiaolin LIANG; Xiaoyu HU; Wuping WANG; Laiyou WANG; Ling YANG; Lexun WANG; Xianglu RONG; Jiao GUO (Journal of Holistic Integrative Pharmacy, 2021)
[Abstract]: Coronavirus disease-2019 (COVID-19) not only causes substantial respiratory pathology, but also results in several extrapulmonary manifestations, including thrombotic complications, myocardial dysfunction and arrhythmia, acute coronary syndromes, acute kidney injury, gastrointestinal symptoms, hepatocellular injury, hyperglycemia and ketosis, neurologicillnesses, ocular symptoms, and dermatologic complications. Given that ACE2, the entry receptor for the causative coronavirus SARS-CoV-2, is expressed in multiple extrapulmonary tissues, direct viral tissue damage is a plausible mechanism of injury. In addition, endothelial damage and thromboinflammation, dysregulation of immune responses, and maladaptation of ACE2-related pathways might all contribute to these extrapulmonary manifestations of COVID-19. Recent reports showed about 2%-11% of patients with COVID-19 had underlying chronic liver diseases. Here we reviewed the liver-specific pathophysiology, presentations and management considerations for patients with COVID-19 to aid clinicians and scientists in recognizing and monitoring the spectrum of manifestations, and in developing research priorities and therapeutic strategies for liver injury in COVID-19.